Penerapan Teknik Budidaya Ikan Dan Tanaman Dalam Ember (Budikdamber) Di Desa Ringinanom Kabupaten Temanggung - M Rafi Muharmawan; M. Trihudiyatmanto; Mufaat Priatmoko; Afna Elfiana; Caliesta Meydina; Zulia Yustina; Liana Dewi; Muhammad Fajar; Aji Dwi Purnama; M Zidni Ilman Nafi'an; Cindi Vidia Nurmasih; M. Elfan Kaukab (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
Yard farming and household livestock are food production businesses by utilizing narrow land. The resulting product can be in the form of plants, vegetables, fish or other food products. Through these activities, everyone is expected to be able to carry out productive activities, namely to produce independent food for daily needs. One of the activities in the aquaculture sector is to do cultivation of damber (cultivating fish and plants in buckets). Fish farming in containers in the form of buckets has advantages, namely that it can be used in narrow areas, drained water from buckets can also be used as liquid fertilizer, and many others, and also has limitations, namely limited production capacity and understanding of the technology. Community Service Activities have one program, namely the application of the Budikdamber technique to the community of Ringinanom Village, Temanggung Regency. Activity methods include preparatory surveys, Technical Guidance, and direct application in the field. Technical guidance is carried out by the service team, while field practice activities are accompanied by members of the activity implementation team. Through this activity, the people of Ringinanom Village have received information and insight about the budikdamber technique. The community has also been facilitated by 30 units of the Budikdamber device package sourced from the Village Government as the realization of the village program in the form of food security.